Assessment of Microplastic Pollution Load and Ecological Risk Index in Surface Water and Sediment Matrices in the Mangrove Ecosystem along Butuan Bay, Southern Philippines : 10.32526/ennrj/23/20240122 - Keleste, Ethel P.; Fedelis, Jolina S.; Opusa, Wendy Faye T.; Inocente, Sherley Ann T.; Banda, Marybeth Hope T.; Latayada, Felmer S.; Jumawan, Joycelyn C.; Vales, Temmy P.; Seronay , Romell A.; Capangpangan, Rey Y. (Environment and Natural Resources Journal, 2025)
Microplastics have garnered attention for their ubiquitous presence across various ecosystems, yet investigations into their occurrence in mangrove environments, particularly in the Philippines, remain minimal and increasingly necessary. This study seeks to establish a foundational understanding of microplastic distribution in Philippine mangrove forests, with a special focus on Butuan Bay. Surface water and sediment samples were collected from mangrove habitats in Butuan City, Buenavista, and Nasipit along Butuan Bay, in the Southern Philippines. Results indicated that Buenavista (BMS) exhibited the highest microplastic concentrations, with mean abundances of 322.22±103.41 MPs/m3 in surface water and 88.89±50.33 MPs/kg in sediments. Both blue and transparent microplastics were prevalent, constituting 24.2% and 25.7% of surface water and 22.6% and 25.7% of sediments, respectively. Microplastics predominantly fell within the 101-250 µm range (46% in surface water and 45.7% in sediments), with films and fragments comprising 69% of surface water MPs and 76.1% of sediment MPs. Ten polymer types were identified, with polypropylene (PP) being the most abundant (31.5% in surface water and 51.7% in sediments). The assessment of the pollution load index (PLI) indicated that MP pollution levels were classified as slightly polluted (hazard level I), and ecological risk index (RI) posed varying degrees across the studied mangroves, ranging from minor danger (hazard level I) to extreme danger (hazard level V). Microplastics were observed to pose ecological risks within these mangrove areas, as indicated by the highest levels of risk shown by BMS and BCMS. Future studies should examine other surrounding waters of Mindanao, such as the adjacent Gingoog Bay, including inland freshwater bodies, to comprehensively assess MP pollution and its potential effects on marine wildlife in the region.